THE ROLE OF THE POLICE TO CURBING ILLEGAL MINING IN LEA VILLAGE, TELLU SIATINGNGE - BONE REGENCY - Asniana Nur (Jurnal Al-Dustur, 2020)
The title of this study is "The Role of the Police to Curbing Illegal Mining in Lea Village, Tellu Siattinge, Bone Regency." The purposes of this research are (1) To find out the authority of the police on preventing illegal mining in Lea Village based on the regulation concerning mineral and coal mining (UU No. 4 Tahun 2009) (2) To find out what are the obstacles of the police on preventing Illegal mining in Lea Village, Tellu Siattinge, Bone Regency.          The type of this research is a qualitative study using sociological and juridical empirical approaches. The primary sources of this research data consist of observations and interviews. The secondary data are derived from documentation and literature reviews such as documents, books, an official statement from the result of researches, whereas the data analysis technique was carried out through three stages, namely: field data collection, data reduction, data presentation, and verification.          The results of this study indicate that: (1) The authority of the police in terms of preventing illegal mining as stated in Regulation Number 2 of 2002 concerning the Indonesian National Police (Undang-Undang Nomor 2 Tahun 2002 tentang Kepolisian Negara Republik Indonesia), that the police have the authority doing investigations and arrests. The duties and authority of the Police are regulated in detail at 13th till 19th Clause. (2) The obstacles of Law Officers (police) in preventing Illegal Mining is still lack of socialization from related parties so that it causes a lack of public awareness of the impacts caused by illegal sand mining in the area of Lea Village, Tellu Siattinge-Bone Regency; distance traveled between the bone resort police station (polres) and the village of Lea takes quite a lot of time and the difficulty of registration procedures/procedures for issuing mining permits.